Messaging solutions in a Linux environment - Putte, Geert van de (IBM redbooks., 2005)
Recently, the adoption of Linux as a platform for business-critical applications has increased significantly. This evolution has also introduced requirements and technologies that were previously not seen in a Linux environment. Messaging and integration products, such as WebSphere MQ and WebSphere BI Message Broker, can now be used on Linux to solve integration problems that include Linux platforms. This IBM Redbooks publication starts with an introduction of messaging and integration technologies to Linux users. It also introduces the world of Linux to people that are familiar with messaging and integration technologies on other platforms. This book ends with a discussion of a few monitoring techniques that can be implemented in a Linux environment, so that a messaging solution can be monitored. Please note that the additional material referenced in the text is not available from IBM.